KUPU-KUPU DALAM KARYA SENI GRAFIS - Nopri Yandri Asri; Irwan Irwan; Yofita Sandra (Serupa The Journal of Art Education, 2020)
The creation of this final work aims to visualize the metamorphosis of butterflies in stencil techniques. This work displays the object of a butterfly that is to social criticism. The embodiment method of this final work goes through five stages: preparation, elaboration, synthesis, concept realization, and completion. Author Successfully Realizing 10 works with the title: new life, sweet, short time, life's journey, freedom, life span, inspiration, survival, generation, and success.Keywords: Butterfly, Graphic Art, Cut Out Stencil Print